EKSPRESI KASPASE 8 DAN PERUBAHAN JUMLAH SEL NEUROGLIA PADA REGULASI MEKANISME APOPTOSISSEL OTAK AKIBAT KERACUNAN MERKURI - Paulus Sugianto, Abdulloh Machin, Hanik Badriyah Hidayati, Moh. Hasan Machfoed (NEURONA, 2013)
INTRODUCTION MERCURY IS A POTENT NEUROTOXIN SINCE IT INDUCES APOPTOSIS AND INFLAMMATORY RESPOND IN BRAIN CASPASES EG CASPASE 8IS ONE OF CENTRAL EFFECTORS OF APOPTOSIS AND SERVE AS SIGNALING MEDIATORS THAT ORCHESTRATE APOPTOTIC EXECUTION PATHWAYS BY CLEAVING A SUBSET OF CELLULAR PROTEINS WHEREAS BRAIN INFLAMMATORY RESPONSE IS TRIGGERED BY THE ACTIVATION OF NEUROGLIAL EG MICROGLIAL CELLS AND ASTROCYTES AND THIS GLIAL REACTIVITY HAS BEEN USED AS AN EARLY MARKER OF NEUROTOXICITYTO STUDY THE EFFECTS OF NEUROTOXICITY MERCURY WE USE CASPASE 8 AND MICROGLIAL AS A PARAMETER OF METHYL MERCURY NEUROTOXICITY